Chromulinavorax destructans, a pathogen of microzooplankton that provides a window into the enigmatic candidate phylum Dependentiae - Deeg, Christoph M.; Zimmer, Matthias M.; George, Emma E.; Husnik, Filip; Keeling, Patrick J.; Suttle, Curtis A. (PLoS pathogens, 2019)
Members of the major candidate phylum Dependentiae (a.k.a. TM6) are widespread across diverse environments from showerheads to peat bogs; yet, with the exception of two isolates infecting amoebae, they are only known from metagenomic data. The limited knowledge of their biology indicates that they have a long evolutionary history of parasitism. Here, we present Chromulinavorax destructans (Strain SeV1) the first isolate of this phylum to infect a representative from a widespread and ecologically significant group of heterotrophic flagellates, the microzooplankter Spumella elongata (Strain CCAP 955/1). Chromulinavorax destructans has a reduced 1.2 Mb genome that is so specialized for infection that it shows no evidence of complete metabolic pathways, but encodes an extensive transporter system for importing nutrients and energy in the form of ATP from the host. Its replication causes extensive reorganization and expansion of the mitochondrion, effectively surrounding the pathogen, consistent with its dependency on the host for energy. Nearly half (44%) of the inferred proteins contain signal sequences for secretion, including many without recognizable similarity to proteins of known function, as well as 98 copies of proteins with an ankyrin-repeat domain; ankyrin-repeats are known effectors of host modulation, suggesting the presence of an extensive host-manipulation apparatus. These observations help to cement members of this phylum as widespread and diverse parasites infecting a broad range of eukaryotic microbes.